TGFβ Signaling in Myeloid Cells Promotes Lung and Liver Metastasis Through Different Mechanisms - Stefanescu, Cristina; Van Gogh, Merel; Roblek, Marko; Heikenwalder, Mathias; Borsig, Lubor (Frontiers in Oncology, 2021)
TGFβ overexpression is commonly detected in cancer patients and correlates with poor prognosis and metastasis. Cancer progression is often associated with an enhanced recruitment of myeloid-derived cells to the tumor microenvironment. Here we show that functional TGFβ-signaling in myeloid cells is required for metastasis to the lungs and the liver. Myeloid-specific deletion of Tgfbr2 resulted in reduced spontaneous lung metastasis, which was associated with a reduction of proinflammatory cytokines in the metastatic microenvironment. Notably, CD8+ T cell depletion in myeloid-specific Tgfbr2-deficient mice rescued lung metastasis. Myeloid-specific Tgfbr2-deficiency resulted in reduced liver metastasis with an almost complete absence of myeloid cells within metastatic foci. On contrary, an accumulation of Tgfβ-responsive myeloid cells was associated with an increased recruitment of monocytes and granulocytes and higher proinflammatory cytokine levels in control mice. Monocytic cells isolated from metastatic livers of Tgfbr2-deficient mice showed increased polarization towards the M1 phenotype, Tnfalpha and Il-1β expression, reduced levels of M2 markers and reduced production of chemokines responsible for myeloid-cell recruitment. No significant differences in Tgfβ levels were observed at metastatic sites of any model. These data demonstrate that Tgfβ signaling in monocytic myeloid cells suppresses CD8+ T cell activity during lung metastasis, while these cells actively contribute to tumor growth during liver metastasis. Thus, myeloid cells modulate metastasis through different mechanisms in a tissue-specific manner.